Perfect Timing for Canakinumab Use in Gout - Hadi Kurniawan Wijaya (Indonesian Rheumatology Associantion, 2024)
Gout is an inflammatory disease caused by the deposition of monosodiumurate (MSU) crystals. Recently, the American College of Rheumatology (ACR)has recommended the usage of interleukin (IL)-1 inhibitor in gout patientswho are refractory to typical anti-inflammatory drugs. An example of IL-1inhibitor is canakinumab. Not much is known regarding the usage ofcanakinumab in gout arthritis. Thus, we decided to conduct a narrativereview that summarizes the efficacy and safety of canakinumab in goutpatients. In this review, we found that canakinumab is superior to nonsteroidal anti-inflammatory drugs (NSAIDs) and corticosteroids in treatingacute gout flares. In addition, canakinumab may also be considered as apreventive therapy for gout flares in patients receiving urate-loweringtherapy. Overall, canakinumab has mild side effects but may occasionallycause serious infections. Canakinumab is also generally safe for use duringpregnancy. Due to the lack of studies, the safety of canakinumab in lactatingwomen, geriatric patients, and patients with hepatic or renal impairment isstill unknown.